WALKING PATHS: THERAPEUTIC ITINERARIES OF WOMEN USING ALCOHOL AND/OR OTHER DRUGS DURING THEIR PREGNANCY-POSTPARTUM CYCLE - Silva, Isabelle Caroline Vitor da; Rodrigues, Ana Vanessa Deffaccio; Neves, Maria Aparecida Moreira das (Revista Uningá, 2021)
Pregnancy, childbirth and postpartum care is provided in accordance with gestational risk factors, such as use of alcohol and/or other drugs by pregnant women. The objective of this study was to trace the therapeutic itinerary of pregnant women who use alcohol and/or other drugs in the health network of a city in the Mid-North of the state of Paraná. This is a qualitative, exploratory study conducted through individual interviews. Firstly, the therapeutic itineraries were built, then the speeches were analyzed in accordance with Bardin and discussed with the aid of current literature. Regarding the therapeutic itinerary, the interviewees accessed primary care, high-risk prenatal care, and hospital services. The results identified two categories: Considerations on the use of alcohol and drugs during pregnancy, and Strengths and weaknesses of the healthcare network’s points of attention. From the statements, probable biological and social implications of using psychoactive substances during pregnancy emerged, such as complications during gestation, fetal alterations, and loss of legal rights over children. As for the points of attention, the importance of multiprofessionality and the role of nursing were highlighted. On the other hand, the network’s disarticulation and professionals’ inability, represented by inappropriate comments and lack of guidance, appear as weakness. It was concluded that it is necessary to provide comprehensive follow-up to pregnant and postpartum women who use alcohol and drugs, with the articulation of the healthcare network and professionals free from judgment to provide a care that meets their biopsychosocial demands.